Spatial scales effects on the geographical origin identification of PGI kiwifruit by stable isotope and mineral elemental fingerprinting - Jiali Li; Jianping Qian; Qian Chen; Zihan Liu; An Li; Xintao Lin; Boyu Shuai; Jiangmin Zhou; Junyi Wang; Zihan Bian; Linghuan Ouyang; Ming Li (Food Control, 2027)

Control of Listeria monocytogenes in fresh-cut chili peppers by bacteriocin paracin wx7-1: Activity, mechanism, and preservative efficacy - Yushu Bian; Jinling Lin; Liuyang Li; Ping Zeng; Honghai Li; Lanhua Yi (Physiological and Molecular Plant Pathology, 2026)

Bioaccumulation, biotransformation and hormesis effects of 6PPD-Q in Eisenia fetida: Impacts on metabolism and gut microbiota - Lin Bian; Wenyan Yu; Hua Yin; Minghan Zhu; Shaoyu Tang; Jingtao Wu; Yuanyuan Yu (Journal of Environmental Sciences, 2026)

Defect engineering oxygen vacancies via synergistic tungsten substitution and water quenching in V2O5 cathodes for high-performance zinc-ion batteries - Jianwei Wang; Lin Xu; Yating Yu; Jianzhao Liu; Qianhui Zhang; Wenlin Zhang; Xinyue Wang; Jihong Bian; Yanzhong Zhen; Daniel Q. Tan (Chemical Engineering Journal, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

An engineered bacteriocin paracin wx7-1 for chili pepper preservation: Controlling soft rot and its dual-target mechanisms - Jinling Lin; Yushu Bian; Tao Lin; Yuze Zheng; Honghai Li; Lanhua Yi (International Journal of Food Microbiology, 2026)

Nitrogen input drives niche partitioning and phylogenetic succession of active ammonia oxidizers in protected vegetable soils - Weishou Shen; Dandan Li; Biyun Bian; Nan Gao; Zhongjun Jia; Xiangui Lin; Xinhua He; Wenhui Zhong (Applied Soil Ecology, 2026)

Dual-color ultrabright AIEgens nanoparticles-based lateral flow immunoassay for simultaneous quantitative detection of serum amyloid A protein and C-reactive protein - Lun Bian; Yuhang Yang; Yu Fu; Kuangrou Jia; Xiangzhou Liu; Xueqing Xu; Yingsong Wu; Fang Hu; Guanfeng Lin (Analytica Chimica Acta, 2026)

Nighttime growth in the green tide alga Ulva prolifera: metabolic basis and ecological implications - Han Xu; Mingzi Lin; Jiaying Bian; Dongyi Yang; Jianan Jiang; Shenyuan Liang; Hao Zhang; Wenrong Zhu; Nianjun Xu; Yahe Li (Journal of Applied Phycology, 2026)

Dynamic modeling and composite anti-disturbance motion control of a ship-borne 3-DOF hybrid motion compensated gangway - Yiqiang Xia; Yangzuobin Ding; Hengdong Bian; Chaoxiong Lin; Jiajia Huang; Songlin Zhou; Xianchao Zhao; Weixing Chen (Ocean Engineering, 2026)

Oxidant-driven vanadium extraction: critical analysis of current methodologies and sustainable practices - Shiyuan Liu; Junlong Wang; Lin Ye; Zhiwei Bian (Minerals Engineering, 2026)

Variations of Corticotropin-Releasing Factor Receptor 1α Contribute to the Blunted HPA Axis Responses to Hypoxia in Plateau Mammals - Jiafang Yang; Fangyuan Xia; Hao Jin; Chatoo Mahanand; Huiqi Lin; Yibin Cao; Jianghui Bian; Dengbang Wei; Eviatar Nevo; Jizeng Du; Shumin Duan; Fang Guo; et al. (Neuroscience Bulletin, 2026)

Integrated LCA-SD modeling for dynamic carbon footprinting in cement production - Yanshuai Wang; Pairui Lin; Xiao Bian; Ruijun Cao; Zhen Leng (Resources, Conservation and Recycling, 2026)

A green integrated process for the valorisation of Chinese quince phenolics: Ultrasound-assisted natural deep eutectic solvent extraction and macroporous resin purification followed by UPLC–TQ–MS/MS-based quality control - Mengyang Hou; Yujuan Zhou; Ka Wing Cheng; Rongrong Luo; Chengyuan Lin; Lin Zhu; Zhaoxiang Bian (Food Chemistry, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Carbon-fiber-grid heated pavement for deicing and snow melting: The role of design parameters and environmental conditions - Xinxing Bian; Huining Xu; Lin Chen; Lin Zhang; Jianhong Ni; Yong Lai (Cold Regions Science and Technology, 2026)

Influence of hydro-mechanical parameter coupling on the dynamic behavior of unsaturated railway subgrades - Shumeng Wu; Liqun Zeng; Jing Hu; Zhongfeng Yang; Hongyang Ke; Xin Ding; Zhihang Lin; Xuecheng Bian (Soil Dynamics and Earthquake Engineering, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Predicting heavy metal impacts on soil ammonia oxidation during sludge land application: An interpretable framework integrating mechanistic models and machine learning - Jianju Li; Xinran Du; Zhiyuan Pan; Lin Si; Huawei Wang; Weihua Li; Rongxing Bian; Yingjie Sun; Liangliang Wei (Journal of Environmental Management, 2026)

NO -driven chemical transformation of terpene mixtures: Linking highly oxygenated organic molecules to health effects in secondary organic aerosol - Xiaowen Chen; Kun Li; Ruiyu Li; Li Fang; Haizhen Bian; Wei Jiang; Caiqing Yan; Lin Du (Journal of Environmental Sciences, 2026)

Precise structural characterization and therapeutic potential of a glucomannan polysaccharide from dried rhizome of plant Bletilla striata against ulcerative colitis - Huidan Hou; Lifeng Li; Tahidul Islam; Jingchun Shi; Mengyang Hou; Siliang Jiang; Xiaohan Zhao; Chengyuan Lin; Quanbin Han; Lin Zhu; Zhaoxiang Bian (Carbohydrate Polymers, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

EuFe-MOF exhibiting excellent peroxidase-like activity and red fluorescence for colorimetric/fluorescence dual-modal sensor to detect xanthine in aquatic products - Zihan Bian; Pei Liu; Guangze Sun; Huan Liu; Ziting Lin; Aihua Liu (Food Chemistry, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

Genome-wide association mapping of native QTLs for Fusarium head blight resistance in US winter wheat - Ruolin Bian; Yaoguang Li; Yanhong Dong; Xiaomao Lin; Guihua Bai (Theoretical and Applied Genetics, 2026)

Contrasting size responses of loricate ciliates to long-term warming: agglutinated forms decrease while hyaline forms increase - Yunfan Zhang; Wenhua Bian; Hanyue Chen; Wuchang Zhang; Chaofeng Wang; Jichen Qiu; Xiaoxia Sun; Jun Lin; Ying Yu; Meiping Feng; Bingzhang Chen (Marine Biology, 2026)

Multiscale analysis reveals key factors governing pesticide residue in staple crop kernels - Chuan Du; Quanzhen Liu; Wenru Bian; Lihua Lin; Yongchang Xie; Weiqing Wang; Na Li; Donghong Wang (Journal of Hazardous Materials, 2026)

Host-specific and community-driven dynamics of plasmid transfer and stability in activated sludge - Ruoxuan Bian; Jiachen Ma; Youshuai Fang; Yiheng Qiao; Zirui Yin; Xuxiang Zhang; Lin Ye (Journal of Hazardous Materials, 2026)

A cascade-responsive fibrous platform combining nanozyme and NO donor therapy for infected diabetic wound healing - Zequn Lin; Fangrong Tan; Zhanglu Lei; Yangtian Bian; Hongtao Qi; Weichang Li; Qianqian Yu (Chemical Engineering Journal, 2026)

A review of advancements in multicellular composites integrated with structural and functional characteristics: design, preparation and properties - Xiaotian Bian; Ting Zheng; Lili Zhang; Chengying Bai; Xiaohong Zhang; Xin Zhang; Lecheng Lin; Kai Shao; Si Shen; Yingjie Qiao; Xiaodong Wang (Chemical Engineering Journal, 2026)

Xenobiotic degradation promotes enrichment but not dissemination of antibiotic resistance genes in activated sludge - Zirui Yin; Jiachen Ma; Ruoxuan Bian; Yiran Wang; Kaoming Zhang; Yanyan Ma; Xuxiang Zhang; Lin Ye (Bioresource Technology, 2026)

Design of a High-Fidelity Motion Data Generator for Unmanned Underwater Vehicles - Li Lin; Hongwei Bian; Rongying Wang; Wenxuan Yang; Hui Li (Journal of Marine Science and Engineering, 2026)
To address the urgent need for high-fidelity motion data for validating navigation algorithms for Unmanned Underwater Vehicles (UUVs), this paper proposes a data generation method based on a parametric motion model. First, based on the principles of rigid body dynamics and fluid mechanics, a decoupled six-degrees-of-freedom (6-DOF) Linear and Angular Acceleration Vector (LAAV) model is constructed, establishing a dynamic mapping relationship between the rudder angle and speed setting commands and motion acceleration. Second, a segmentation–identification framework is proposed for three-dimensional trajectory segmentation, integrating Gaussian Process Regression and Ordering Points To Identify the Clustering Structure (GPR-OPTICS), along with a Dynamic Immune Genetic Algorithm (DIGA). This framework utilizes real vessel data to achieve motion segment clustering and parameter identification, completing the construction of the LAAV model. On this basis, by introducing sensor error models, highly credible Inertial Measurement Unit (IMU) data are generated, and a complete attitude, velocity, and position (AVP) motion sequence is obtained through an inertial navigation solution. Experiments demonstrate that the AVP data generated by our method achieve over 88% reliability compared with the real vessel dataset. Furthermore, the proposed method outperforms the PSINS toolbox in both the reliability and accuracy of all motion parameters. These results validate the effectiveness and superiority of our proposed method, which provides a high-fidelity data benchmark for research on underwater navigation algorithms.

Integrated assessment of ecological environment quality in the eastern coastal zone of Hainan Island (China) using GIS and the analytic hierarchy process - Kaizhe Fu; Jiyong Ma; Lin Zhou; Xiaolei Liu; Yue Gou; Mingguang He; Shiyou Zhang; Dayu Bian; Jianhua Guo (Frontiers in Marine Science, 2026)
Introduction The core eastern coastal cities of Qionghai and Wanning on Hainan Island are facing escalating pressures on their ecological integrity and biodiversity due to intensifying human activities. Methods To evaluate the regional ecological environmental quality, this study established a comprehensive assessment framework based on a systematic analysis of local ecological-geological conditions. Multiple factors across topographic, geologic, hydrologic, pedologic, and anthropogenic dimensions—including topography, stratigraphy, water and soil quality, land use, and ecosystem type—were integrated. Using the Delphi method to determine factor weights and ArcGIS for spatial analysis. Results The assessment revealed that human activity is the dominant influence. The area was classified into four ecological quality categories: excellent, good, moderate, and poor. Notably, key coastal aquaculture zones such as Wancheng Town, Dongao Town, and Xiaohai Bay in Wanning were identified as having relatively poor ecological quality. Discussion/conclusion Consequently, future coastal management must prioritize regulating ecological risk in human-disturbed areas, enhancing pollution control in aquaculture, and strengthening land-use policies to foster sustained regional ecological improvement.

Evaluation of UAV and satellite platforms for gross primary production monitoring under different model frameworks in agroecosystems - Xiaolong Hu; Jiang Bian; Liangsheng Shi; Lin Lin; Shenji Li; Xianzhi Deng; Jinmin Li; Chenye Su; Shuai Du; Tinghan Wang; Yujie Wang (Computers and Electronics in Agriculture, 2026)

Predicting the occurrence of the emerging disinfection byproducts halocyclopentadienes and analyzing their driving factors in nationwide tap water using machine learning - Yongchang Xie; Quanzhen Liu; Tianhao Liu; Lihua Lin; Rong Li; Chuan Du; Wenru Bian; Donghong Wang (Water Research, 2026)

Simultaneous stabilization of As/Pb and enhancement of nitrogen retention in farmland soil by the novel Fe-Mn oxidizing bacteria co-inoculation - Xiaofang Ouyang; Zhanyu Guo; Lin Bian; Zhi Dang; Meiying Xu; Hua Yin (Journal of Hazardous Materials, 2026)

Monoterpenes amplify the oxidative potential of biomass burning secondary aerosols - Xiaowen Chen; Kun Li; Haizhen Bian; Shan Zhang; Xueqi Ma; Li Fang; Wei Jiang; Caiqing Yan; Lin Du (Journal of Hazardous Materials, 2026)

Dual influences of the allergenicity of Atlantic cod parvalbumin fermented by Lactobacillus helveticus - Shuai Ma; Xitong Yu; Hao Wang; Liwei Wang; Tingyu Zhang; Yumiao Bian; Mengxin Wang; Zhenxing Li; Ziye Zhang; Hong Lin (Food Bioscience, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Zero-valent iron embedded biochar-based hydrogel composites for nitrate removal in heterogeneous water-sediment system: Overlooked role of microbial community - Xinnan Pan; Xing Hou; Bian Yao; Li Lin; Wei He; Longfei Wang (Journal of Water Process Engineering, 2025)

A distinctive merocyanine-based fluorescent probes for the detection of phosgene and hydrazine - Wen-Ke Jiang; Xu Wang; Wei-Na Wu; Lin-Yan Bian; Yun-Chang Fan; Yuan Wang; Zhi-Hong Xu; Lintao Zeng (Journal of Hazardous Materials, 2025)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

Rational design of molybdenum carbide loaded Fe3O4 for rapid and repeated water disinfection: Photothermal effect and bactericidal mechanisms - Tingting Jiang; Sihui Bian; Siyu Huang; Guanbo Wang; Xinyue Song; Lin Zhu (Journal of Environmental Chemical Engineering, 2025)

Nano-sized heterogeneous photocatalyst Fe3O4@V/TiO2-catalyzed synthesis and antimycobacterial evaluation of 2-substituted benzimidazoles - Lijian Bao; Xiaodong Chen; Yanli Li; Guangyuan Zhu; Jingjun Wang; Mingyue Chen; Xingyu Bian; Qiang Gu; Yumin Zhang; Feng Lin (Molecular Diversity, 2025)

One-year observation of cloud condensation nuclei concentration in a coastal city in eastern China: Seasonal variations, wet deposition, and regional transport - Zihan Wang; Yishu Bian; Qing Duan; Honglei Wang; Zihao Wu; Yue Ke; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2025)

Integrated, self-powered humidity/iontronic pressure sensors for complex respiratory pattern recognition - Senrong Ye; Junxian Li; Haowei Kong; Zijun Pan; Haohan Wu; Zhanghao Lin; Chenchen Bian; Gengzhe Shen; Chi Zhang; Weidong Song; Zheng Liu; Xin He (Chemical Engineering Journal, 2025)

TPM3–NTRK1 fusion confers resistance to osimertinib in lung adenocarcinoma: a model in a continuous cell line - Fang Cao; Jiayin Dai; Kun Dong; Zhenli Yang; Yanli Zhu; Changsong Qi; Dongmei Lin; Xiaocui Bian; Yuqin Liu (Human Cell, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Non-extractant recycling of Ti, Fe, Ca and Al as value-added anatase, hematite, gypsum and nordstrandite from waste red mud - T. Su; S. Li; R. Bian; Y. Lin; S. Zhu (International Journal of Environmental Science and Technology, 2025)

Improved DeepLabV3+ and GR-ConvNet for shiitake mushroom harvest robots flexible grasping of mimicry - Xiong Yin; Lin Yang; Daojin Yao; Xin Yang; Yinbing Bian; Yuhua Gong (Computers and Electronics in Agriculture, 2025)

Assessing the effect of perfluoroalkyl and polyfluoroalkyl substances on cardiovascular-kidney-metabolic syndrome: Insights from an interpretable machine learning model - Zidan Zheng; Yuyan Xu; Ning Kang; Yiwen Dong; Xin Wang; Lin Zhang; Hongying Bian; Qibing Zeng (Science of The Total Environment, 2025)

Effects of organic selenium on metabolic responses and disease resistance in rose plants - Yanli Bian; Xiangyang Li; Deliang Gao; Guofu Zhang; Aijuan Zhang; Yizhi Feng; Zhiwei Hua; Lin Liang (Journal of Hazardous Materials, 2025)

Hydrogels with anti-inflammatory modulation microniches for tendon repair - Tao Zhou; Tao Ma; Qiankun Wang; Zifu Wang; Jun Huang; Lin Zhong; Ding Zhou; Zhe Jin; Yang Niu; Dong Yin; Tianyou Hu; Yujie Bian; et al. (Chemical Engineering Journal, 2025)

Primary colorectal cancer cells cultured in hydrogel microcapsules-integrated microfluidic chip for chemotherapy evaluation - Chuanmeng Pan; Xiang Lin; Feika Bian; Liqun Li; Xian Shen (Chemical Engineering Journal, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Using machine learning algorithm to predict lighting energy consumption of daylight-linked lighting systems from spatial daylight autonomy - Yu Bian; Yuan Zhou; Shiying Yang; Dandan Lin; Yuan Ma (Energy and Buildings, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Infrared Laser Stimulation of Purkinje Cells Primarily Depends on TRP Channel Activation - Bin-Bin Dong; Chen Wang; Wan-Qi Huang; Yu-Peng Bian; Jun Liu; Wei Chen; Lin Zhou; Ying Shen; Luxi Wang (Neuroscience Bulletin, 2025)

In-situ supramolecular self-assembly strategy to fabricate carbon-doped g-C3N4 microtubes: Efficient photocatalytic removal of antibiotics and bacterial inactivation - Hua Lei; Changhao Bian; Fengyu Guo; Xingning Xiao; Ruibin Hu; Jianhan Lin; Wen Wang; Hua Yang; Xiaoping Dong (Journal of Environmental Chemical Engineering, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Corrigendum to “Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents” [Food Packaging and Shelf Life 46 (2024) 101361] - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2025)

Enhancing anaerobic digestion of swine manure using microbial electrolysis cell and microaeration - Yanqiang Di; Wenxue Hou; Chunlin Bian; Tianlong Zheng; Benyi Xiao; Lin Li (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Green valorization of Chaenomelis Fructus agro-industrial by-products as a source of phenolics: Ultrasound-assisted extraction, adsorptive enrichment and quality control - Mengyang Hou; Yujuan Zhou; Chengyuan Lin; Jingchun Shi; Huidan Hou; Yanhua Ma; Lin Zhu; Zhaoxiang Bian (Food Chemistry, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Enhancing hydrogen sorption kinetics of Ti-based hydrogen storage alloy tanks through an optimized bulk-powder combination strategy - Liansen Bian; Longfei Shao; Bolun Wang; Jiaqi Zhang; Yinghui Li; Zhigang Hu; Jianxin Zou; Kemin Zhang; Xi Lin (Chemical Engineering Journal, 2025)

Exosomal miRNA reprogramming in pyroptotic macrophage drives silica-induced fibroblast-to-myofibroblast transition and pulmonary fibrosis - Lin Zhang; Jiaqi Tian; Ning Li; Yongheng Wang; Yulan Jin; Hongying Bian; Min Xiong; Zitong Zhang; Jiahua Meng; Zhengpu Han; Shuyin Duan (Journal of Hazardous Materials, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Lithological impact on topsoil organic carbon storage of karst forest soils shaped by aggregate pool complexity and their molecular composition - Qingmei Lin; Shuotong Chen; Xiao Feng; Thammavongsa Sounilan; Kun Cheng; Xuhui Zhang; Rongjun Bian; Xiaoyu Liu; Yan Wang; Marios Drosos; Jufeng Zheng; Lianqing Li; et al. (Applied Soil Ecology, 2025)

Comprehensive analysis of different GNSS receivers performance based on PPP-AR and positioning accuracy during 22 geomagnetic storms in 2023 - Zhuang Chen; Xiaomin Luo; Xinmei Liang; Yujie Li; Yingzong Lin; Shaofeng Bian (Advances in Space Research, 2025)

Biofilm formation dynamics in long-distance water conveyance pipelines: Impacts of nutrient levels and metal stress - Yifan Hu; Ruiting Li; Kaiqin Bian; Qing Zhou; Yang Pan; Lin Ye; Aimin Li; Peng Shi (Water Research, 2025)

Responses of farmland soil organic carbon to key natural and landscape factors: Threshold effects and nonlinearity - Xiaochen Liu; Falong Lin; Zhenxing Bian (Journal of Cleaner Production, 2025)

The heterointerface engineering triggers hydrogen spillover through synergistic effect in alkaline media - Qiang Zhang; Yuhong Bian; Sunpeng Shan; Zhiwei Shu; Nana Wang; Xiao Zhang; Yanchao Xu; Hongjun Lin; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2025)

Microeukaryotic communities varied along the gradient in the seaweed habitats: A case study in a typical reef island in the East China Sea - Meiping Feng; Yijia Yang; Yunfan Zhang; Jichen Qiu; Wenhua Bian; Yifan Chen; Siting Hu; Kai Wang; Jian Zhang; Jun Lin; Shouyu Zhang (Regional Studies in Marine Science, 2024)

Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2024)

Estimating potato aboveground biomass using unmanned aerial vehicle RGB imagery and analyzing its relationship with tuber biomass - Yanran Ye; Liping Jin; Chunsong Bian; Guolan Xian; Yongxin Lin; Jiangang Liu; Huachun Guo (Field Crops Research, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Composted maize straw under fungi inoculation reduces soil N2O emissions and mitigates the microbial N limitation in a wheat upland - Rong Zhou; Hui Wang; Jingru Zhang; Zhe Chen; Penghui Jin; Tianlong Hu; Qing Bian; Xingwu Lin; Xueqiang Zhao; Zubin Xie (Science of The Total Environment, 2024)

CFD simulation of the aerodynamic performance of co-axial multi-rotor wind turbines using the actuator line method - Saixian Bian; Yuan Zhang; Xin Cai; Shifa Lin; Yazhou Wang; Xingwen Guo (Ocean Engineering, 2024)

Soil organic carbon sequestration can be promoted through the improvement of landscape configuration heterogeneity in typical agricultural regions of northeast China - Xiaochen Liu; Falong Lin; Zhenxing Bian; Zhichao Dong (Journal of Environmental Management, 2024)

Using magnesium hydride as the future dual-mode propellant for spacecraft: A simulation investigation - Xi Lin; Ze Zhang; Lianshen Bian; Longfei Shao; Yinglong Kang; Keming Zhang; Jianxin Zou (Chemical Engineering Journal, 2024)

The nexus of solar absorption and morphology designs based on 2D photothermal materials: From rational design to advanced application of water purification - Tingting Jiang; Sihui Bian; Yu Wang; Xiaorui Fan; Lin Zhu; Xinyue Song; Guanbo wang; Tianhao Wang; Haifeng Zhang (Chemical Engineering Journal, 2024)

Light attenuation parameterization in a highly turbid mega estuary and its impact on the coastal planktonic ecosystem - Qiyinan Lin; Zhixuan Feng; Yihe Wang; Xue Wang; Zhaoxuan Bian; Fan Zhang; Fang Cao; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2024)
Light is essential for phytoplankton photosynthesis and many other biogeochemical processes in the aquatic system. However, light regimes vary greatly in the estuaries and coasts due to the optical complexity of the Case-2 waters. In this study, observed vertical profiles of photosynthetically active radiation (PAR; 400-700 nm) in a highly turbid mega estuary, the Changjiang (Yangtze River) Estuary, are used to quantify the effects of sedimentary and biogeochemical components on PAR attenuation in the water column and associated ecological impacts. The in-situ data suggest suspended sediment plays the most crucial role in light diffuse attenuation coefficient (K d ) distribution, followed by salinity (i.e., an index for colored dissolved organic matter) and phytoplankton chlorophyll-a. A new parameterization of K d , based on suspended sediment, chlorophyll-a concentration, and salinity, is fitted using multiple linear regression. The previous and new K d parameterizations are further applied to a coupled hydrodynamics-sediment-ecosystem model to simulate spring phytoplankton blooms. Comparative model runs reveal that the new K d parameterization resulted in a better representation of the spring bloom patterns in magnitude, horizontal distribution, and vertical thickness of the high chlorophyll-a band offshore the turbidity maximum zone during the spring bloom. In summary, accurate representations of underwater light fields in the optically complex Case-2 water are critical in understanding biophysical processes that control planktonic ecosystem dynamics in the estuaries and coastal seas.

Synergetic control analysis of CO2 and air pollutants in the automobile manufacturing industry in Guangdong-Hong Kong-Macao Greater Bay area: The supply chain perspective - Mingliang Liu; Jingjing Yin; Jianyi Lin; Fanxin Meng; Jian Tao; Yahui Bian; Alexandre Tuyishimire; Huaqing Li; Yanyan Zhang; Kai Wang (Journal of Cleaner Production, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

Flexible sensor based on conformable, sticky, transparent elastomers for electronic skin - Xinxin Cai; Xinqi Wang; Fuping Bian; Jiayi Li; Ruixiang Zhou; Jiwen Hu; Shudong Lin (Chemical Engineering Journal, 2024)

Sensitive dual-channel lateral flow immunoassay tagged with high brightness latex microsphere for simultaneous detection of respiratory viral antigens - Tao Dong; Guangze Sun; Zhonghuang Yang; Yiming Jiao; Jinze Li; Ziting Lin; Xin Zhang; Zihan Bian; Aihua Liu (Chemical Engineering Journal, 2024)

Assembly of 3D printed N-doped biochar as impeller with CaCO3 as sacrificial pore generator for enhanced dye adsorption - Zining Zhou; Kaiji Xu; Changyong Li; Jianbin Lin; Juanjuan Bian; Kang Sun; Jianchun Jiang; Shu-Feng Zhou; Guowu Zhan (Chemical Engineering Journal, 2024)

Experimental study on wood chips gasification over Ni/dolomite - Zhiyuan Luo; Ye Tian; Lin Mi; Guanyan Chen; Xiong Zhou; Ao Bian (Clean Technologies and Environmental Policy, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Bioactive metabolite profiles and quality of Rosa rugosa during its growing and flower-drying process - Yanli Bian; Jinju Pan; Deliang Gao; Yizhi Feng; Bingjie Zhang; Le Song; Lei Wang; Xingang Ma; Lin Liang (Food Chemistry, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

CO2 mineralization and utilization by tailings sand in China for potential carbon sinks and spatial project layout - Huaqing Li; Yahui Bian; Mingliang Liu; Jianyi Lin; Min Dai; Hongyi Xie; Huajun Yu; Bin Chen; Meili Xue; Zhiwei Li; Jingjing Yin; Liming Xue (Resources, Conservation and Recycling, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

High-throughput analysis of hazards in novel food based on the density functional theory and multimodal deep learning - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Wenwen Bian; Haizhen Mo (Food Chemistry, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

One-step enrichment of phenolics from Chaenomeles speciosa (Sweet) Nakai fruit using macroporous resin: Adsorption/desorption characteristics, process optimization and UPLC-QqQ-MS/MS-based quantification - Mengyang Hou; Chengyuan Lin; Yanhua Ma; Jingchun Shi; Jie Liu; Lin Zhu; Zhaoxiang Bian (Food Chemistry, 2024)

Stenotrophomonas maltophilia contributes to smoking-related emphysema through IRF1-triggered PANoptosis of alveolar epithelial cells - Haibo Xia; Jiaheng Lin; Yue Wang; Jinyan Yu; Hailan Wang; Cheng Cheng; Yi Yang; Tao Bian; Yan Wu; Qizhan Liu (Environmental Pollution, 2024)

Dual modification engineering enabled efficient perovskite solar cells with high open-voltage of 1.233 V - Zhongqi Liu; Long Shao; Fancong Zeng; Shuhang Bian; Bin Liu; Yuqi Wang; Yanjie Wu; Yongzhi Shao; Huan Zhang; Yuhong Zhang; Zhicong Shi; Xue Bai; et al. (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

A novel hybrid modelling framework for GPP estimation: Integrating a multispectral surface reflectance based Vcmax25 simulator into the process-based model - Xiaolong Hu; Liangsheng Shi; Lin Lin; Shenji Li; Xianzhi Deng; Li Li; Jiang Bian; Xie Lian (Science of The Total Environment, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

PM2.5 air quality and health gains in the quest for carbon peaking: A case study of Fujian Province, China - Yahui Bian; Xiaobo Huang; Shuifa Lin; Hui Han; Jinsheng Chen; Jianyi Lin; Xinxin Ye (Science of The Total Environment, 2024)

Satellite observations reveal a decreasing albedo trend of global cities over the past 35 years - Shengbiao Wu; Xingwen Lin; Zunjian Bian; Mathew Lipson; Raffaele Lafortezza; Qiang Liu; Sue Grimmond; Erik Velasco; Andreas Christen; Valéry Masson; Ben Crawford; Helen Claire Ward; et al. (Remote Sensing of Environment, 2024)

The double-edged sword effect of indigo naturalis - Yiqi Xu; Chengyuan Lin; Hor-Yue Tan; Zhao-xiang Bian (Food and Chemical Toxicology, 2024)

Oil mistparticulate matter exposure induces hyperlipidemia-related inflammation via microbiota/ SCFAs/GPR43 axis inhibition and TLR4/NF-κB activation - Huanliang Liu; Huipeng Nie; Yue Shi; Wenqing Lai; Liping Bian; Lei Tian; Kang Li; Zhuge Xi; Bencheng Lin (Environmental Pollution, 2024)

A mild and efficient sonothermal tumor therapy enhanced by sonodynamic effect with biodegradable red phosphorus nanoparticles - Zhizi Ma; Meng Yuan; Ziyong Cheng; Zhuang Yang; Ling Yang; Bin Liu; Yulong Bian; Abdulaziz A. Al Kheraif; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2024)

Ubiquitination-specific protease 7 enhances stemness of hepatocellular carcinoma by stabilizing basic transcription factor 3 - Mingchao Hu; Chengchen Dai; Xieyin Sun; Yinqi Chen; Nuo Xu; Zhaoyi Lin; Shiyu Xu; Chun Cheng; Zhonghua Tan; Saiyan Bian; Wenjie Zheng (Functional & Integrative Genomics, 2024)

Mechanical and thermal effects of Asian topography on northern East Asian low - Zhongda Lin; Cholaw Bueh; Bian He (Climate Dynamics, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Formation mechanism and quantitative risk analysis of the landslide-induced hazard chain by an integrated approach for emergency management: A case study in the Bailong River basin, China - Yan Chong; Guan Chen; Xingmin Meng; Shiqiang Bian; Fengchun Huang; Linxin Lin; Dongxia Yue; Yi Zhang; Fuyun Guo (CATENA, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

mitfa deficiency promotes immune vigor and potentiates antitumor effects in zebrafish - Wan-Ping Bian; Shao-Lin Xie; Chao Wang; Grigoriy G. Martinovich; Yan-Bo Ma; Pan-Pan Jia; De-Sheng Pei (Fish & Shellfish Immunology, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Microbial electrolysis cell simultaneously enhancing methanization and reducing hydrogen sulfide production in anaerobic digestion of sewage sludge - Xiangyu Chen; Benyi Xiao; Xinyi Tang; Chunlin Bian; Junxin Liu; Lin Li (Chemosphere, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

Performance enhancement of integrating microbial electrolysis cell on two-stage anaerobic digestion of food waste: Electro-methanogenic stage versus electro-two stages - Tianlong Zheng; Chunlin Bian; Benyi Xiao; Xiangyu Chen; Juan Wang; Lin Li (Bioresource Technology, 2023)

Population Pharmacokinetics and Pharmacogenetics Analyses of Dasatinib in Chinese Patients with Chronic Myeloid Leukemia - Shiyu He; Jinxia Zhao; Jialu Bian; Yinyu Zhao; Yuanyuan Li; Nan Guo; Lei Hu; Boyu Liu; Qianhang Shao; Huan He; Lin Huang; Qian Jiang (Pharmaceutical Research, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

CAS FGOALS-f3-L Model Datasets for CMIP6 DCPP Experiment - Shuai Hu; Bo Wu; Yiming Wang; Tianjun Zhou; Yongqiang Yu; Bian He; Pengfei Lin; Qing Bao; Hailong Liu; Kangjun Chen; Shuwen Zhao (Advances in Atmospheric Sciences, 2023)
The outputs of the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System (FGOALS-f3-L) model for the decadal climate prediction project (DCPP) of the Coupled Model Intercomparison Project Phase 6 (CMIP6) are described in this paper. The FGOALS-f3-L was initialized through the upgraded, weakly coupled data assimilation scheme, referred to as EnOI-IAU, which assimilates observational anomalies of sea surface temperature (SST) and upper-level (0–1000-m) ocean temperature and salinity profiles into the coupled model. Then, nine ensemble members of 10-year hindcast/forecast experiments were conducted for each initial year over the period of 1960–2021, based on initial conditions produced by three initialization experiments. The hindcast and forecast experiments follow the experiment designs of the Component-A and Component-B of the DCPP, respectively. The decadal prediction output datasets contain a total of 44 monthly mean atmospheric and oceanic variables. The preliminary evaluation indicates that the hindcast experiments show significant predictive skill for the interannual variations of SST in the north Pacific and multi-year variations of SST in the subtropical Pacific and the southern Indian Ocean.

Study on effect of equivalent initial water content on dredged sludge treated by VP-FSCM - Xiaoya Bian; Haodong Yang; Kun Duan; Rongjun Zhang; Lin Wu (Transportation Geotechnics, 2023)

Simultaneous biohythane and volatile fatty acids production from food waste in microbial electrolysis cell-assisted acidogenic reactor - Chunlin Bian; Xiangyu Chen; Juan Wang; Benyi Xiao; Rongzhan Liu; Lin Li; Jianguo Liu (Journal of Cleaner Production, 2023)

Improving sewage sludge dewaterability via heterogeneous activation of persulfate by Fe–Al layered double hydroxide: Role of generated SO4−• - Benyi Xiao; Xiangyu Chen; Ke Zhang; Tianlong Zheng; Chunlin Bian; Jianguo Liu; Lin Li; Junxin Liu (Journal of Environmental Management, 2023)

Molybdenum-Induced Apoptosis of Splenocytes and Thymocytes and Changes of Peripheral Blood in Sheep - Shu-gang Cui; Yu-ling Zhang; Hong-wei Guo; Bian-hua Zhou; Er-jie Tian; Jing Zhao; Lin Lin; Hong‑wei Wang (Biological Trace Element Research, 2023)

Daphnane-type diterpenoids from Stellera chamaejasme L. and their inhibitory activity against hepatocellular carcinoma cells - Zhuo-Yang Cheng; Jing-Xian Ren; Xiao-Bian Xue; Man Wang; Xiao-Qi Yu; Bin Lin; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

The attenuated live vaccine strain W2512 provides protection against novel variant infectious bursal disease virus - Mei Leng; Xiaomeng Bian; Yazheng Chen; Zhishan Liang; Jiamin Lian; Meng Chen; Feng Chen; Zhanxin Wang; Wencheng Lin (Archives of Virology, 2023)

Soy protein isolate-citrus pectin-gallic acid ternary composite high internal phase Pickering emulsion for delivery of β-carotene: Physicochemical, structural and digestive properties - Xinyu Xu; Lin Li; Chunmin Ma; Dan Li; Yang Yang; Xin Bian; Jing Fan; Na Zhang; Feng Zuo (Food Research International, 2023)

Enhancing streamflow estimation by integrating a data-driven evapotranspiration submodel into process-based hydrological models - Xie Lian; Xiaolong Hu; Jiang Bian; Liangsheng Shi; Lin Lin; Yuanlai Cui (Journal of Hydrology, 2023)

Taurine reduces apoptosis mediated by endoplasmic reticulum stress in islet β-cells induced by high-fat and -glucose diets - Dongdong Zhao; Xiaozhou Zhang; Yongxin Bian; Lu Meng; Yutong Wu; Yidi Ma; Chen Li; Jingjing Wang; Zizheng Fu; Jingyuan Dai; Deqi Yin; Shumei Lin; et al. (Food and Chemical Toxicology, 2023)

Discrete element model for moisture diffusion of rocks during water absorption - Yanan Chen; Kang Bian; Wei Zhang; Jian Liu; Fei Ai; Zhenping Liu; Lin Chen (Computers and Geotechnics, 2023)

The parametric uncertainty estimation of water and nitrogen transport simulation in a paddy field experiment using HYDRUS‐1D - Jianmin Bian; Juanjuan Wu; Siyu Nie; Yu Wang; Xiaosheng Lin (Irrigation and Drainage, 2023)
The HYDRUS model is an efficient technical means to study the process of complex nitrogen (N) transport in farmland. Nonetheless, spatial variability in soil water and N parameters has been observed at the field scale, leading to uncertainties in the HYDRUS model. In this study, the HYDRUS‐1D model was corrected and verified by the measured data. Generalized likelihood uncertainty estimation (GLUE) was used to estimate the uncertainty and sensitivity of the model parameters. The differences in simulated and measured data were expressed in terms of root mean square error, normalized root mean square error and coefficient of determination, and the model calibration and verification indicated that the result was reliable. The soil saturated water content, dispersion and sorption coefficient were well identified, with values ranging from 0.42 to 0.45 cm 3 /cm 3 , 0.26 to 0.29 cm and 0.141 to 0.158 L/mg, respectively. The denitrification rate and saturated hydraulic conductivity greatly influenced the uncertainty in the model results. Considering the uncertainty of the parameters, the predicted leaching of N accumulation from 0 to 100 cm depth ranged from 9.5 to 12.7 kg/ha. The HYDRUS‐1D model can simulate water and N transport in paddy fields. The prediction interval can be narrowed by considering the uncertainty of the model parameters.

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

Discovery of novel ascorbic acid derivatives and other metabolites in fruit of Rosa roxburghii Tratt through untargeted metabolomics and feature-based molecular networking - Yaqi Zhang; Xiqing Bian; Guanyu Yan; Baoqing Sun; Wen Miao; Mingzheng Huang; Na Li; Jian-Lin Wu (Food Chemistry, 2023)

Cross-species binding spectrum of ACE2 to SARS-CoV-2 RBD - Xihao Liao; Changge Guan; Chenghua Wang; Xinjie Chen; Xiaomei Lin; Lianghua Lu; Lu Li; Ting Wang; Nan Su; Bian Wu; Xinquan Wang; Chong Zhang; et al. (Science China Life Sciences, 2023)

Multiscale numerical simulation of CO2 hydrate storage using machine learning - Alan Junji Yamaguchi; Toru Sato; Takaomi Tobase; Xinran Wei; Lin Huang; Jia Zhang; Jiang Bian; Tie-Yan Liu (Fuel, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Immunomodulatory Biomaterials and Emerging Analytical Techniques for Probing the Immune Micro-Environment - Nanyan Bian; Chenyu Chu; Shengan Rung; Vicha Huangphattarakul; Yi Man; Jie Lin; Chen Hu (Tissue Engineering and Regenerative Medicine, 2023)

Stimulus-responsive hydrogels: A potent tool for biosensing in food safety - Xiaoxiao Lin; Zhiguang Wang; Xuexia Jia; Ruipeng Chen; Yingkai Qin; Yalan Bian; Wei Sheng; Shuang Li; Zhixian Gao (Trends in Food Science & Technology, 2023)

Origin traceability of bottled mineral water imported into China using chemical and stable isotope fingerprints - Hao Wu; Haiquan Chen; Bingqing Yi; Karyne M. Rogers; Xuehai Bian; Ni Lin; Xiuwen Zhou; Baohui Jin; Zhi Yan; Haichao Zhou (Journal of Hydrology, 2023)

Residue behaviors, processing factors and transfer rates of pesticides and metabolites in rose from cultivation to consumption - Yanli Bian; Yizhi Feng; Aijuan Zhang; Xiaoxue Qi; Xingang Ma; Jinju Pan; Jifeng Han; Lin Liang (Journal of Hazardous Materials, 2023)

Meniscus inspired flexible superhydrophobic coating with remarkable erosion resistance for pipeline gas transmission - Xuerui Zang; Xuewen Cao; Weiwei Zheng; Tianxue Zhu; Yonggang Lei; Jianying Huang; Zhong Chen; Lin Teng; Jiang Bian; Yuekun Lai (Chemical Engineering Journal, 2023)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

High-Throughput Identification of Antihypertensive Peptides (AHTPs) and Characterization of AHTP-Derived Genes in the Lined Seahorse (Hippocampus erectus) - Yu Huang; Xiyang Chen; Haoyue Shu; Panpan Xiao; Xueqiang Lin; Junmin Xu; Chao Bian; Xinxin You; Jian Yang; Qiong Shi (Frontiers in Marine Science, 2022)
Recently, the prevalence of hypertension has become a global challenge. Therefore, tremendous efforts have been made to identify and purify antihypertensive peptides (AHTPs) from food-derived proteins to aid the discovery of new hypotensive drugs with fewer side effects. In this study, we performed high-throughput prediction of AHTPs based on multi-omics data, providing an overview of AHTPs in the lined seahorse proteins and suggesting their potential application as bioactive agents to lower blood pressure. We identified 14,695 AHTP-derived genes in the lined seahorse, and most of them were supported by transcriptomic evidence, whereas only 495 genes were further detected by proteome sequencing. Among these predicted AHTP-derived genes, the longest titin had the most hits with 104 AHTPs, some of which were clustered in exon 158, 194, and 204. Another AHTP-rich group was in the collagen family, and four AHTP-rich collagens exhibited much higher transcription in the pouch than in other examined tissues, including brain, testis, and embryos. Additionally, antihypertensive triplets, comprised of the permutations of Gly, Pro, and Lys, prevailed in all collagen sequences due to the representative XaaYaaGly repeat units. In summary, our present findings provide a solid basis for understanding the abundance of various AHTPs in the lined seahorse as well as shed light on the development of antihypertensive products and drugs using seahorses as an important resource.

Estrogen Deficiency Aggravates Fluoride-Induced Liver Damage and Lipid Metabolism Disorder in Rats - Ya-ming Yu; Bian-hua Zhou; Yi-lin Yang; Cheng-Xiang Guo; Jing Zhao; Hong-wei Wang (Biological Trace Element Research, 2022)

Post-failure evolution analysis of an irrigation-induced loess landslide using multiple remote sensing approaches integrated with time-lapse ERT imaging: lessons from Heifangtai, China - Shiqiang Bian; Guan Chen; Runqiang Zeng; Xingmin Meng; Jiacheng Jin; Linxin Lin; Yi Zhang; Wei Shi (Landslides, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Simulation study on the migration of F− in soil around Chagan Lake, China - Peng Xu; Jianmin Bian; Juanjuan Wu; Yihan Li; Jialin Li; Xia Zeng; Zuo Lin (Environmental Science and Pollution Research, 2021)

Temporal and spatial diagnostic model of vehicle gas pollutants - Qizhou Hu; Lishuang Bian; Juanjuan Lin (Environmental Monitoring and Assessment, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Datasets for the CMIP6 Scenario Model Intercomparison Project (ScenarioMIP) Simulations with the Coupled Model CAS FGOALS-f3-L - Shuwen Zhao; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Yuyang Guo; Lijuan Hua; Kangjun Chen; Xiaowei Wang (Advances in Atmospheric Sciences, 2021)
The datasets for the tier-1 Scenario Model Intercomparison Project (ScenarioMIP) experiments from the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System model, finite-volume version 3 (CAS FGOALS-f3-L) are described in this study. ScenarioMIP is one of the core MIP experiments in phase 6 of the Coupled Model Intercomparison Project (CMIP6). Considering future CO 2 , CH 4 , N 2 O and other gases’ concentrations, as well as land use, the design of ScenarioMIP involves eight pathways, including two tiers (tier-1 and tier-2) of priority. Tier-1 includes four combined Shared Socioeconomic Pathways (SSPs) with radiative forcing, i.e., SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5, in which the globally averaged radiative forcing at the top of the atmosphere around the year 2100 is approximately 2.6, 4.5, 7.0 and 8.5 W m −2 , respectively. This study provides an introduction to the ScenarioMIP datasets of this model, such as their storage location, sizes, variables, etc. Preliminary analysis indicates that surface air temperatures will increase by about 1.89°C, 3.07°C, 4.06°C and 5.17°C by around 2100 under these four scenarios, respectively. Meanwhile, some other key climate variables, such as sea-ice extension, precipitation, heat content, and sea level rise, also show significant long-term trends associated with the radiative forcing increases. These datasets will help us understand how the climate will change under different anthropogenic and radiative forcings.

Simulation and Improvements of Oceanic Circulation and Sea Ice by the Coupled Climate System Model FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Bo An; Shuwen Zhao; Lijuan Hua (Advances in Atmospheric Sciences, 2020)

CAS-FGOALS Datasets for the Two Interglacial Epochs of the Holocene and the Last Interglacial in PMIP4 - Weipeng Zheng; Yongqiang Yu; Yihua Luan; Shuwen Zhao; Bian He; Li Dong; Mirong Song; Pengfei Lin; Hailong Liu (Advances in Atmospheric Sciences, 2020)
Two versions of the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System model (CAS-FGOALS), version f3-L and g3, are used to simulate the two interglacial epochs of the mid-Holocene and the Last Interglacial in phase 4 of the Paleoclimate Modelling Intercomparison Project (PMIP4), which aims to study the impact of changes in orbital parameters on the Earth’s climate. Following the PMIP4 experimental protocols, four simulations for the mid-Holocene and two simulations for the Last Interglacial have been completed, and all the data, including monthly and daily outputs for the atmospheric, oceanic, land and sea-ice components, have been released on the Earth System Grid Federation (ESGF) node. These datasets contribute to PMIP4 and CMIP6 (phase 6 of the Coupled Model Intercomparison Project) by providing the variables necessary for the two interglacial periods. In this paper, the basic information of the CAS-FGOALS models and the protocols for the two interglacials are briefly described, and the datasets are validated using proxy records. Results suggest that the CAS-FGOALS models capture the large-scale changes in the climate system in response to changes in solar insolation during the interglacial epochs, including warming in mid-to-high latitudes, changes in the hydrological cycle, the seasonal variation in the extent of sea ice, and the damping of interannual variabilities in the tropical Pacific. Meanwhile, disagreements within and between the models and the proxy data are also presented. These datasets will help the modeling and the proxy data communities with a better understanding of model performance and biases in paleoclimate simulations.

Overview of the CMIP6 Historical Experiment Datasets with the Climate System Model CAS FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Shuwen Zhao; Xiaowei Wang (Advances in Atmospheric Sciences, 2020)
The three-member historical simulations by the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System model, version f3-L (CAS FGOALS-f3-L), which is contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6), are described in this study. The details of the CAS FGOALS-f3-L model, experiment settings and output datasets are briefly introduced. The datasets include monthly and daily outputs from the atmospheric, oceanic, land and sea-ice component models of CAS FGOALS-f3-L, and all these data have been published online in the Earth System Grid Federation (ESGF, https://esgf-node.llnl.gov/projects/cmip6/ ). The three ensembles are initialized from the 600th, 650th and 700th model year of the preindustrial experiment (piControl) and forced by the same historical forcing provided by CMIP6 from 1850 to 2014. The performance of the coupled model is validated in comparison with some recent observed atmospheric and oceanic datasets. It is shown that CAS FGOALS-f3-L is able to reproduce the main features of the modern climate, including the climatology of air surface temperature and precipitation, the long-term changes in global mean surface air temperature, ocean heat content and sea surface steric height, and the horizontal and vertical distribution of temperature in the ocean and atmosphere. Meanwhile, like other state-of-the-art coupled GCMs, there are still some obvious biases in the historical simulations, which are also illustrated. This paper can help users to better understand the advantages and biases of the model and the datasets.

Noninvasive ultrasound deep brain stimulation of nucleus accumbens induces behavioral avoidance - Lili Niu; Yanchen Guo; Zhengrong Lin; Zhe Shi; Tianyuan Bian; Lin Qi; Long Meng; Anthony A. Grace; Hairong Zheng; Ti-Fei Yuan (Science China Life Sciences, 2020)

Characterization of bimetallic Fe/Ni nanoparticles supported by amphiphilic block copolymer and its application in removal of 1,1,1-trichloroethane in water - Kai Huang; Hao Bian; Meng Zhang; Cong Zhan; Can Li; Wei Zhang; Changzheng Cui; Qiang Lu; Kuangfei Lin; Jianhua Zhao (Environmental Science and Pollution Research, 2020)

Cu(OH)2 nanorods undergo sulfidation in water: in situ formation of CuO nanorods as intermediates and enhanced toxicity to Escherichia coli - Heming Su; Xiaoting Qian; Zhouhang Gu; Zhenlan Xu; Haijin Lou; Xinyun Bian; Tao Zeng; Daohui Lin; Juliane Filser; Lingxiangyu Li (Environmental Chemistry Letters, 2020)

Modeling the Impacts of Nitrogen Dynamics on Regional Terrestrial Carbon and Water Cycles over China with Noah-MP-CN - Jingjing Liang; Zong-Liang Yang; Xitian Cai; Peirong Lin; Hui Zheng; Qingyun Bian (Advances in Atmospheric Sciences, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Correction to: Particulate matter 2.5 induced arrhythmogenesis mediated by TRPC3 in human induced pluripotent stem cell-derived cardiomyocytes - Cheng Cai; Min Ling; Jiayi Huang; Yongping Lin; Weilun Miao; Pei Chen; Xing Chen; Jiaxian Wang; Minglong Chen; Qian Bian (Archives of Toxicology, 2019)

Helmert transformation solutions combination and update with new measurements - Shengquan Li; Bing Ji; Guobin Chang; Peng Lin; Shaofeng Bian (Acta Geodaetica et Geophysica, 2019)

Bioinformatics Analysis of Microarray Profiling Identifies That the miR-203-3p Target Ppp2ca Aggravates Seizure Activity in Mice - Lifang Zhang; Yanran Li; Xuexue Ye; Lin Bian (Journal of Molecular Neuroscience, 2018)

Paleoseismic study of the Kamishiro Fault on the northern segment of the Itoigawa–Shizuoka Tectonic Line, Japan - Aiming Lin; Mikako Sano; Maomao Wang; Bing Yan; Di Bian; Ryoji Fueta; Takashi Hosoya (Journal of Seismology, 2017)

Regulation of peroxisome proliferator-activated receptor gamma on milk fat synthesis in dairy cow mammary epithelial cells - Lili Liu; Ye Lin; Lixin Liu; Lina Wang; Yanjie Bian; Xuejun Gao; Qingzhang Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Health risk assessment of heavy metals in soil-plant system amended with biogas slurry in Taihu basin, China - Bo Bian; Cheng Lin; Lin Lv (Environmental Science and Pollution Research, 2016)

Lack of association between polymorphisms in interleukin (IL)-12, IL-12R, IL-23, IL-23R genes and Takayasu arteritis in a Chinese population - Kun-Qi Yang; Yan-Kun Yang; Xu Meng; Ying Zhang; Xiong-Jing Jiang; Hai-Ying Wu; Hui-Min Zhang; Lei Song; Jin Bian; Dan Wen; Lin-Ping Wang; Xian-Liang Zhou (Inflammation Research, 2016)

The phytotoxic effects of selenium–mercury interactions on root growth in Brassica rapa (LvLing) - Zhi-Wei Bian; Jian Chen; Hui Li; Dan-Dan Liu; Li-Fei Yang; Yue-Lin Zhu; Wen-Li Zhu; Wei Liu; Zheng-Zheng Ying (Horticulture, Environment, and Biotechnology, 2016)

Structure of summer atmospheric boundary layer in the center of Arctic Ocean and its relation with sea ice extent change - LinGen Bian; MingHu Ding; Xiang Lin; ChangGui Lu; ZhiQiu Gao (Science China Earth Sciences, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Health risk assessment of metals in food crops and related soils amended with biogas slurry in Taihu Basin: perspective from field experiment - Bo Bian; Hai suo Wu; Lin Lv; Yamin Fan; Haiming Lu (Environmental Science and Pollution Research, 2015)

Effect of Excessive Potassium Iodide on Rat Aorta Endothelial Cells - Man Zhang; Xiaoyan Zou; Xinying Lin; Jianchao Bian; Huicui Meng; Dan Liu (Biological Trace Element Research, 2015)

Risk assessment of heavy metals in air, water, vegetables, grains, and related soils irrigated with biogas slurry in Taihu Basin, China - Bo Bian; Ling Jun Zhou; Lei Li; Lin Lv; Ya Min Fan (Environmental Science and Pollution Research, 2015)

A chimeric antibody targeting CD147 inhibits hepatocellular carcinoma cell motility via FAK-PI3K-Akt-Girdin signaling pathway - Yuan Wang; Lin Yuan; Xiang-Min Yang; Ding Wei; Bin Wang; Xiu-Xuan Sun; Fei Feng; Gang Nan; Ye Wang; Zhi-Nan Chen; Huijie Bian (Clinical & Experimental Metastasis, 2015)

Pore structure effect on reservoir electrical properties and well logging evaluation - Huan-Lin Bian; Ju Guan; Zhi-Qiang Mao; Xiao-Dong Ju; Gui-Qing Han (Applied Geophysics, 2014)

Association between vacA genotypes and the risk of duodenal ulcer: a meta-analysis - Bei-Bei Zhang; Yong Li; Xue-Qiang Liu; Pei-Jian Wang; Bo Yang; Dong-Lin Bian (Molecular Biology Reports, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Formation, regeneration, and transformation of protoplasts of Streptomyces diastatochromogenes 1628 - Zheng Ma; Jinxiu Liu; Xiaozhen Lin; Xuping Shentu; Yalin Bian; Xiaoping Yu (Folia Microbiologica, 2014)

Effect of Combined Excess Iodine and Low-Protein Diet on Thyroid Hormones and Ultrastructure in Wistar Rats - Jie Gao; Xinying Lin; Xihua Liu; Qun Yang; Zhijie Zhang; Qingwu Jiang; Jianchao Bian (Biological Trace Element Research, 2013)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

The vertical structure of the atmospheric boundary layer over the central Arctic Ocean - Lingen Bian; Yongfeng Ma; Changgui Lu; Xiang Lin (Acta Oceanologica Sinica, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

Preliminary Functional Analysis of the Isoforms of OsHsfA2a (Oryza sativa L.) Generated by Alternative Splicing - Hongtian Wang; Mingdi Bian; Zhenming Yang; Chentao Lin; Wuliang Shi (Plant Molecular Biology Reporter, 2013)

Transcription factor OsAP21 gene increases salt/drought tolerance in transgenic Arabidopsis thaliana - Xiaofeng Jin; Yong Xue; Ren Wang; RanRan Xu; Lin Bian; Bo Zhu; Hongjuan Han; Rihe Peng; Quanhong Yao (Molecular Biology Reports, 2013)

Identification of a new gene encoding 5-enolpyruvylshikimate-3-phosphate synthase using genomic library construction strategy - Chang-Yan Zhou; Yong-Sheng Tian; Zhi-Sheng Xu; Wei Zhao; Chen Chen; Wen-Hua Bao; Lin Bian; Run Cai; Ai-Zhong Wu (Molecular Biology Reports, 2012)

Interdecadal change in the Antarctic Circumpolar Wave during 1951–2010 - Lingen Bian; Xiang Lin (Advances in Atmospheric Sciences, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

The vertical structure and seasonal changes of atmosphere ozone and temperature at Zhongshan Station over East Antarctica - LinGen Bian; Zhong Lin; DongQi Zhang; XiangDong Zheng; LongHua Lu (Science China Earth Sciences, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Cloning the human SUMO1 promoter - Angela Nanos-Webb; Adeline Deyrieux; Xue-lin Bian; Germán Rosas-Acosta; Van G. Wilson (Molecular Biology Reports, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Cloning and Expression of lipP, A Gene Encoding a Cold-Adapted Lipase from Moritella sp.2-5-10-1 - Xiuxia Yang; Xuezheng Lin; Tingjun Fan; Ji Bian; Xiaohang Huang (Current Microbiology, 2008)

Geochemical Environment and Health Problems in China - Nian-Feng Lin; Jie Tang; Jian-Min Bian (Environmental Geochemistry and Health, 2004)

Characteristics of Environmental Geochemistry in the Arseniasis Area of the Inner Mongolia of China - Nian-Feng Lin; Jie Tang; Jian-Min Bian (Environmental Geochemistry and Health, 2002)

Characteristics of micrometeorology in the surface layer in the Tibetan Plateau - Liu Huizhi; Zhang Hongsheng; Bian Lin’gen; Chen Jiayi; Zhou Mingyu; Xu Xiangde; Li Shiming; Zhao Yijun (Advances in Atmospheric Sciences, 2002)